Vitamin B1, B6, Chronotype, and Sleep Duration in Patient with Neurotic, Stress and Somatoform Disorders - Pertiwi, Lintang Mega; Fanani, Mohammad; Hikmayani, Nur Hafidha (Jurnal Kesehatan Masyarakat, 2024)
Sleep disorders are prevalent among individuals with neurotic, stress, and somatoform disorders. Nonetheless, the essential roles of vitamin B1 and B6 in sleep regulation and the insights provided by chronotype on circadian rhythms, and their interplay remains undiscovered in existing research. This study investigates the relationship between vitamin B1 and B6 levels, chronotype, and sleep duration in patients with neurotic, stress, and somatoform disorders. This study took time from December 2022 to January 2023 and recruited 42 patients diagnosed with neurotic, stress, and somatoform disorders and whoever willingly participated in the research. Vitamin B1 and B6 levels were measured using the Liquid Chromatography tandem-mass spectrometry (LC-MS-MS) method, while Chronotype was assessed using the Morningness Eveningness Questionnaire (MEQ). Sleep duration data were collected through structured interviews. The results found no statistically significant relationship between vitamin B1 and B6 levels, chronotype, and sleep duration. However, bivariate analysis revealed significant associations with monthly income (OR=0.21; 95% CI=0.05-0.94; p=0.042) and duration of diagnosis (OR=3.90; 95% CI=1.06-14.38; p=0.041), though this association did not persist in multivariate analysis.